Displaced or Depressed? The Effect of Working in Automatable Jobs on Mental Health - Sylvie Blasco; Julie Rochut; Benedicte Rouland (Institute of Labor Economics (IZA), 2022)
Automation may destroy jobs and change the labour demand structure, thereby potentially impacting workers' health and well-being. Using French individual survey data, we estimate the effects of working in automatable jobs on mental health. Implementing propensity score matching to solve the issue of endogenous exposure to automation risk, we find that workers whose job is at risk of automation in the future are about 4 pp more likely to suffer at present from severe mental disorders. Fear of job loss within the year and fear of qualification or occupational changes seem relevant channels to explain our findings.
Keywords: I10; J24; 330; mental health; automation; job insecurity; propensity score matching